Analysis of pulmonary hydatid cysts underwent surgery - Durkan, Atilla; Ozturk, Bulent; Cakmak, Muharrem (Scientific Publishers of India, 2018)
Introduction: Hydatid cyst is a parasitic disease caused by Echinococcus granulosus. The liver and lungs are the most frequently involved organs. The treatment of lung hydatid disease is surgery. We aimed to discuss the results of surgically treated patients with pulmonary hydatid cysts in light of the related literature. Materials and method: 85 patients were divided into two groups as complicated and non-complicated. Patients who had more than one cyst in the same lobe or patients with multiple lung cysts in different locations were excluded in the study. The significance of the results was assessed by Fisher's exact test. P values <0.05 were considered as significant. Findings: While the number of non-complicated patients was 58 (68%), it was 27 (32%) for complicated patients. In the statistical analysis, gender difference was not significant for both groups (p>0.05). Additionally, the disease was not significant in terms of right or left lung location (p>0.05). For both groups, the disease was not significant in terms of the location of lobe. Statistically, gender was found to be not significant onon bronchus or pleural expanding (for male p>0.05, for female p>0.05). But, the right lung lesions were found to be significant in terms of the expansion in both bronchus and pleura (p<0.05). Centrally located lesions were found to be statistically significant in terms of bronchial expansion (p<0.05). Discussion: Hydatid disease is particularly common in places where farming is still widespread. We believe that the only treatment method is people’s awareness and surgical procedures. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Complicated; Cyst; Non-complicated; Surgery